Engaging large classes of higher education students: a combination of spaced learning and team-based learning - Carlos, Vânia; Rodrigues, Mário; Matos, Bárbara; Gonçalves, Lurdes; Ribeiro, Fernando; Fardilha, Margarida (Frontiers in Education, 2023)
We are in an era where keeping the students focused and interested can be challenging. Furthermore, it is relevant, in avoiding students’ dropout and increasing students’ achievements, to research on how student engagement can be nurtured and, how is this aspect influenced by the teacher attitude and the teaching and learning (T&L) approaches. With the purpose of engaging a large Biochemistry class of first year students (n = 170 in the pilot study and n = 147 in the full project) from the Biomedical Sciences degree from the University of Aveiro in Potugal, a combination of two different learning methodologies was implemented: Team-based Learning (TBL) and Spaced Learning (SL). The main objectives of this pedagogical innovation were to promote collaboration between students, to keep students engaged throughout the semester and to keep the teacher satisfaction through the students’ participation in class and positive feedback. A typical class involved various steps which combine different flavors of TBL and SL: bibliography was provided one week in advance to the students for them to get familiarized with it; in class, the students answered an individual quiz, followed by a group quiz; the next step was solving a problem. Meanwhile a SL break occurred in which students did distracting activities (usually physical activities). Lastly, a short seminar in the form of Q&A occurred to clarify all the doubts. The assessment of this class involved different individual and group components. Qualitative and quantitative data were collected through focus group interviews, questionnaires, and observation techniques. After analyzing the results, we can conclude that globally students seem to prefer learning with TBL and SL than with traditional methodologies. Students emphasized the SL as a positive strategy. Furthermore, they acknowledge that teacher attitude was crucial for their engagement.